Endothelin Level and Its Correlation with Uric Acid in Type 2 Diabetic Multiuse Patients - Zahraa Majid Ismail; Zyad Hussein Jawad; Ali Jasim Hammood (Al-Mustansiriyah Journal of Science)
This research aims to find the direct linkage among the Uric acid rates with Endothelin (ET-1), which is considered the indication of endothelial dysfunction or endothelial damage in patients with T2-DM. This study, included 96 patients with T2-DM and 96 controls, the mean age ranged (56.73 ± 9.14), (56.42 ± 8.74) respectively. Results showed a highly significant increase in Endothelin (ET-1) levels, uric acid, urea, and systolic blood pressure (SBP) was observed as compared with the control group, while Diastolic blood pressure (DBP) and body mass (BMI) were not substantially increased. Additionally, a significant positive correlation was found between ET-1 with uric acid, urea, SBP, DBP in patients with T2-DM (p < 0.05). Finally, elevated uric acid levels in older people who have chronic blood pressure are one of the factors influencing the increased release of ET-1, thus the development of cardiovascular disease.